Establishing Student Character Through The Implementation of Multicultural Values - Aryati, Ani; Suroso, suroso (IAIN Ponorogo, 2022)
This study investigates the implementation of multicultural values and students' character formation at the Faculty of Law. This study used experimental research with quasi-experimental. The sampling technique used cluster sampling. Primary data sources were students. Then, researchers gave multiple-choice item tests using the Likert Scale. The data interview was gathered from the Dean and Lecturers of AIK. Secondary data was obtained from documentation and literature. The research gave a pre-test and treated multicultural values. The data collection is in tests, non-tests (Likert scale), observations, interviews, and documentation. Data analyzed by t-test Independent-Sample T-Test. The finding shows that the character of the students of the Faculty of Law, University of Muhammadiyah, Palembang, experienced a significant increase after the application of multicultural values. The researchers conducted the study in moral knowing by applying the values of tolerance, democratic values, the values of equality, and the values of justice. The implication of these values makes Law Faculty students know moral values, have awareness and understand a good point of view. Second, researchers provide two-week student day activities in mosques, sports fields, and classrooms. During student day, the value of multicultural education is instilled. The effect obtained after student day is that students of the Faculty of Law have empathy, humility, and self-esteem. The third is moral action by conducting inter-religious dialogue in developing social intelligence. Implementing multicultural values – moral knowing, feeling, and action can shape students' character in everyday life.